2008
DOI: 10.1182/blood-2007-09-111872
|View full text |Cite
|
Sign up to set email alerts
|

The recurrent SET-NUP214 fusion as a new HOXA activation mechanism in pediatric T-cell acute lymphoblastic leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is mostly characterized by specific chromosomal abnormalities, some occurring in a mutually exclusive manner that possibly delineate specific T-ALL subgroups. One subgroup, including MLLrearranged, CALM-AF10 or inv (7)(p15q34) patients, is characterized by elevated expression of HOXA genes. Using a gene expression-based clustering analysis of 67 T-ALL cases with recurrent molecular genetic abnormalities and 25 samples lacking apparent aberrations, we identified 5 new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(192 citation statements)
references
References 45 publications
8
183
1
Order By: Relevance
“…74 We and others have used SNP, BAC or oligo-array CGH platforms to identify deletions resulting to dysregulated expression of TAL1 38 and LMO2, 75 deletion of RB1, 38 deletion and mutation of PTEN, 38,76,77 deletion or mutation of the U3 ubiquitin ligase FBXW7, 76,78 amplification of MYB 38,79,80 and fusion of SET to NUP214. 81 T-ALL thus exhibits the similar genetic complexity to that observed in B-ALL. Studies integrating analysis of CNA, sequence mutations (for example, NOTCH1 18 and PTEN 77 ) will be important to accurately classify T-ALL and examine associations with treatment outcome.…”
Section: Genomic Analysis Of T-lineage Allmentioning
confidence: 60%
“…74 We and others have used SNP, BAC or oligo-array CGH platforms to identify deletions resulting to dysregulated expression of TAL1 38 and LMO2, 75 deletion of RB1, 38 deletion and mutation of PTEN, 38,76,77 deletion or mutation of the U3 ubiquitin ligase FBXW7, 76,78 amplification of MYB 38,79,80 and fusion of SET to NUP214. 81 T-ALL thus exhibits the similar genetic complexity to that observed in B-ALL. Studies integrating analysis of CNA, sequence mutations (for example, NOTCH1 18 and PTEN 77 ) will be important to accurately classify T-ALL and examine associations with treatment outcome.…”
Section: Genomic Analysis Of T-lineage Allmentioning
confidence: 60%
“…Juxtaposition with TCRB regulatory elements via translocation (7;7)(p15;q34) or inversion(7)(p15q34) directly activates HOXA by a cis-like mechanism; 12,13 however, the majority of HOXA locus deregulation has been described to occur in trans. Fusion proteins that arise from rearrangements involving the Mixed Lineage Leukemia gene (MLL) 4 , MLLT10 (formerly AF10) [14][15][16][17] and the SET-NUP214 translocation 18 have been shown to recruit DOT1 Ligand (DOT1L), which stimulates HOXA expression through aberrant methylation of Lys79 of Histone H3. 19,20 DOT1L is additionally known to methylate a range of target genes that are also likely to contribute to the leukemic phenotype, 21 and it is therefore probable that the molecular mechanisms of leukemogenesis within the HOXA Pos subgroup are heterogeneous.…”
Section: An Early Thymic Precursor Phenotype Predicts Outcome Exclusimentioning
confidence: 99%
“…These symptoms were in line with those of acute undifferentiated leukemia. Furthermore, van Vlierberghe et al (13) reported set-can gene fusion in T-cell acute lymphoblastic leukemia. These authors found that the fusion protein appeared to promote an elevated expression of the HOXA cluster genes (homeobox A, HOXA), which are key genes involved in hematopoietic stem cell proliferation and differentiation, that may cause leukemia, such as T-cell acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted to encode a 277 amino acid protein with a molecular weight of 39 kDa. The set gene has been found to play a role in leukemia and ovarian cancer, but its role in the development of colorectal adenocarcinoma and oral squamous cell carcinoma remains to be elucidated (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%